Spray dryer processed graphene oxide/reduced graphene oxide for high‐performance supercapacitor. Issue 4 (6th May 2020) - Karakoti, Manoj; Jangra, Ritu; Pandey, Sandeep; Dhapola, Pawan Singh; Dhali, Sunil; Mahendia, Suman; Singh, Pramod K; Sahoo, Nanda Gopal
Abstract: This study deals with the utility of mini spray dryer process to improve the dispersibility, of graphene oxide(GO) and its application for high‐performance supercapacitor. Initially, the neutral solution of GO was obtained using the modified Hummer's method. After this, the prepared GO solution was processed by mini spray dryer to obtain a more purified, lighter, and dispersed form of GO which is named as spray dryer processed GO (SPGO). The SPGO thus obtained showed excellent dispersibility behavior with various solvents, which is not found in case of conventional oven drying. Furthermore, utility of SPGO and its reduced form (r‐SPGO) for supercapacitor applications have been investigated. Results obtained from the cyclic voltammetry(CV) analysis, impedance, and charge‐discharge behavior of supercapacitor fabricated using r‐SPGO shows enhanced features. Therefore, the simple spray dried GO and its reduced form, that is, r‐SPGO can be utilized as a potential candidate for the supercapacitor application. Herein, as synthesized SPGO exhibited the specific capacitance of 12.07 and 37.6 F/g with PVA‐H3 PO4 and 1 mol/L H3 PO4, respectively, at a scan rate of 5 mV/s. On the other hand, reduced form of SPGO, that is, r‐SPGO showed the specific capacitance of 27.16 and 230 F/g with PVA‐H3 PO4 and 1 mol/L H3 PO4, respectively.